Students’ level of science process skills acquisition and academic achievement during the pandemic - Asio, John Mark R.; Mondejar, Christian U. (2022)
In the middle of the pandemic, most schools adopted the blended learning modality. As a result, dealing with the "New Normal" presented difficulties for private schools. This study aims to analyze the level of acquisition in science process skills of private junior high school students and its relationship to students' academic achievement in the subject. The researchers used a convenience sampling technique and a descriptive-correlational research design for 105 students. The researchers created and content-validated an instrument for students' acquisition and academic achievement to gather the data. With the help of SPSS 23, the study used descriptive and inferential statistics. The study showed that communicating skills got the highest and measuring skills got the lowest score. In addition, the study observed significant differences in the communication skills and academic achievements of students when grouped according to gender. Furthermore, there was also a significant difference in the students' responses in measuring skills and classifying skills when grouped according to monthly household income. Finally, there was a moderately positive relationship between science process skills acquisition and academic achievement. The researchers suggested recommendations for teachers, school heads, and the institution to help improve the students' science process skills.
Keywords: Academic achievement; COVID-19 pandemic